A Virtual Makeup Augmented Reality System - Borges, Aline; Morimoto, Carlos (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2019: Anais do XXI Simpósio de Realidade Virtual e Aumentada, 2019)
Virtual makeup systems allow users to try makeup on remotely, without wasting products or spending time cleaning up later. Some virtual makeup systems just show the final makeup result on the user’s face, while other systems allow some interaction when applying makeup on a photo. In this paper we introduce an augmented reality system that allows users to apply virtual makeup directly on their face using a physical applicator, simulating a virtual mirror experience. Facial features are detected and tracked using an RGBD camera and mapped to a normalized 2D facial mesh composed of 124 triangles. Finger touches on the face are also detected on the RGBD video stream, and used to store the applied makeup texture representation on the corresponding 2D facial triangle. Rendering the face with the virtual makeup is performed by back-projecting the makeup stored on the facial mesh to the image captured by the camera. Our initial prototype demonstrates the feasibility of our technique, that detects touches very accurately (about 2.2 mm), and that achieves real-time interactive performance (about 15 fps) when tracking and rendering makeup using a regular PC and an Intel RealSense RGBD camera.